1998
DOI: 10.1016/s0550-3213(98)00283-1
|View full text |Cite
|
Sign up to set email alerts
|

Bubbles in the supersymmetric standard model

Abstract: We compute the tunneling probability from the symmetric phase to the true vacuum, in the first order electroweak phase transition of the MSSM, and the corresponding Higgs profiles along the bubble wall. We use the resummed two-loop temperature-dependent effective potential, and pay particular attention to the light stop scenario, where the phase transition can be sufficiently strongly first order not to wipe off any previously generated baryon asymmetry. We compute the bubble parameters which are relevant for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
181
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(189 citation statements)
references
References 61 publications
8
181
0
Order By: Relevance
“…Again, a possible two-stage phase transition persists, in agreement with previous results [20,33]. We remark that the qualitative effects of increasingà t remain unchanged with respect to the case of m Q = 300GeV.…”
Section: Resultssupporting
confidence: 91%
“…Again, a possible two-stage phase transition persists, in agreement with previous results [20,33]. We remark that the qualitative effects of increasingà t remain unchanged with respect to the case of m Q = 300GeV.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies have found L w ∼ (20 − 30)T −1 in the MSSM [8] and L w ∼ (2 − 40)T −1 in extensions of the MSSM [33,35].…”
Section: Quantum Boltzmann Equationsmentioning
confidence: 85%
“…This method avoids making any a priori ansatz about the functional form or power counting of G(k, x). 8 …”
Section: Solution To the Flavored Boltzmann Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kink ansatz in many situations is a good approximation but it might be interesting to have a more refined description and to determine which deviations occur in the presence of potentials depending on two or more Higgs fields and one or more CP violating phases [13][14][15][16]. In fact it turns out that the most important value in the MSSM is the deviation ∆β = max v [v(β(v)−β(v c ))]/v c from the straight line between the minima since the baryon asymmetry is [17,18] proportional toHaving the exact profile one can calculate the baryon asymmetry like [17] * e-mail: P.John@thphys.uni-heidelberg.de and investigate the dynamics of expanding bubbles as in refs. [19][20][21].…”
mentioning
confidence: 99%